Assessing and facilitating complex sentence formulation in picture description tasks. - Marinellie SA (Advances in Speech Language Pathology, 2006)
Assessment in speech-language pathology often involves an evaluation of a child's ability in sentence formulation. The primary objective of the study was to explore the priming effect on syntactic production in school-age children with specific language impairment (SLI). Priming is the tendency to use syntactic forms that have recently been spoken or heard. A total of 18 children with SLI and 18 typically-developing children participated in a task that involved formulating sentences about pictures in a prime condition and a no-prime condition for relative clauses and adverbial clauses. A significant priming effect was found for adverbial clauses, but not for relative clauses. Results emphasize the importance in the assessment of syntactic knowledge for children with language impairments. Future research is required to better understand how priming techniques may be used for children with language impairments.